Characterization of centromeric histone H3 (CENH3) variants in cultivated and wild carrots (Daucus sp.). - Frank Dunemann (Public Library of Science (PLoS), 2014)
In eukaryotes, centromeres are the assembly sites for the kinetochore, a multi-protein complex to which spindle microtubules are attached at mitosis and meiosis, thereby ensuring segregation of chromosomes during cell division. They are specified by incorporation of CENH3, a centromere specific histone H3 variant which replaces canonical histone H3 in the nucleosomes of functional centromeres. To lay a first foundation of a putative alternative haploidization strategy based on centromere-mediated genome elimination in cultivated carrots, in the presented research we aimed at the identification and cloning of functional CENH3 genes in Daucus carota and three distantly related wild species of genus Daucus varying in basic chromosome numbers. Based on mining the carrot transcriptome followed by a subsequent PCR-based cloning, homologous coding sequences for CENH3s of the four Daucus species were identified. The ORFs of the CENH3 variants were very similar, and an amino acid sequence length of 146 aa was found in three out of the four species. Comparison of Daucus CENH3 amino acid sequences with those of other plant CENH3s as well as their phylogenetic arrangement among other dicot CENH3s suggest that the identified genes are authentic CENH3 homologs. To verify the location of the CENH3 protein in the kinetochore regions of the Daucus chromosomes, a polyclonal antibody based on a peptide corresponding to the N-terminus of DcCENH3 was developed and used for anti-CENH3 immunostaining of mitotic root cells. The chromosomal location of CENH3 proteins in the centromere regions of the chromosomes could be confirmed. For genetic localization of the CENH3 gene in the carrot genome, a previously constructed linkage map for carrot was used for mapping a CENH3-specific simple sequence repeat (SSR) marker, and the CENH3 locus was mapped on the carrot chromosome 9.